2009
DOI: 10.1371/journal.pntd.0000398
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin F Cysteine Protease of the Human Liver Fluke, Opisthorchis viverrini

Abstract: BackgroundThe liver fluke Opisthorchis viverrini is classified as a class I carcinogen due to the association between cholangiocarcinoma and chronic O. viverrini infection. During its feeding activity within the bile duct, the parasite secretes several cathepsin F cysteine proteases that may induce or contribute to the pathologies associated with hepatobiliary abnormalities.Methodology/Principal FindingsHere, we describe the cDNA, gene organization, phylogenetic relationships, immunolocalization, and functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
55
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 55 publications
7
55
0
Order By: Relevance
“…Sripa and Kaewkes (2000a) observed an intense inflammatory response in areas of the biliary epithelium where parasite antigens were present, particularly those tissues in contact with the fluke. Moreover, numerous studies have provided evidence, albeit with low-resolution microscopy, that fluke antigens are detected inside cholangiocytes lining the biliary epithelium in O. viverrini- infected hamsters (Sripa and Kaewkes, 2000a; Pinlaor et al, 2009; Smout et al, 2009). Until now, the mechanism by which liver fluke antigens are internalised by cholangiocytes remained elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Sripa and Kaewkes (2000a) observed an intense inflammatory response in areas of the biliary epithelium where parasite antigens were present, particularly those tissues in contact with the fluke. Moreover, numerous studies have provided evidence, albeit with low-resolution microscopy, that fluke antigens are detected inside cholangiocytes lining the biliary epithelium in O. viverrini- infected hamsters (Sripa and Kaewkes, 2000a; Pinlaor et al, 2009; Smout et al, 2009). Until now, the mechanism by which liver fluke antigens are internalised by cholangiocytes remained elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that cysteine proteases are secreted into ES products suggests that act as digestive agents in the intestine. A recent study on cathepsin F of O. viverrini revealed enzyme in epithelial cells lining the bile ducts of infected animals, which suggested to possibility that it may stimulate biliary epithelium inflammation and proliferation and promote cholangiocarcinogenesis [57]. Hence, the extracorporeal roles of the cysteine proteases of C. sinensis warrant further investigation.…”
Section: Proteasesmentioning
confidence: 99%
“…Genomic and proteomic analysis of several major global helminth parasites have revealed that parasite-derived proteases are key virulence factors [44][45][46][47][48][49][50][51][52]. The proteases of helminth parasites play numerous indispensable roles in parasite physiology, such as, in protein processing and the turnover of parasite proteins, and in various pathogenic aspects, such as, the facilitation of parasite penetration or invasion into host tissue, the hydrolysis of host proteins for nutrient uptake, and host immune system modulation [46,[53][54][55][56][57][58][59]. Accordingly, their activities are essential for parasite survival and growth, which suggests that they are attractive targets for vaccines or chemotherapeutic agents [53,[60][61][62][63].…”
Section: Proteasesmentioning
confidence: 99%
“…However, it has been predicted that the N-terminal region of human procathepsin F has a cystatin-like fold (Nägler et al, 1999). Cathepsin F from the human liver fluke, Opisthorchis viverrini, lacks a region corresponding to the cystatin-like domain (Pinlaor et al, 2009). …”
Section: Primary Structure Analysis Of Mscpi Precursor Proteinmentioning
confidence: 99%